2005
DOI: 10.1021/bi048288i
|View full text |Cite
|
Sign up to set email alerts
|

Coulombic and Hydrophobic Interactions in the First Intracellular Loop Are Vital for Bradykinin B2 Receptor Ligand Binding and Consequent Signal Transduction

Abstract: The role of the first intracellular loop (IC1) in the function of the rat bradykinin B2 receptor (BKB2R) was probed. On the basis of the bovine rhodopsin X-ray structure, the BKB2R IC1 consists of six residues: (60)HKTNCT. Exchange of this sequence with the bradykinin B1 receptor IC1 (PRRQLN) resulted in a chimera which bound bradykinin and signaled as wild-type (WT) BKB2R. In contrast, a chimera containing the IC1 of rat angiotensin II type Ia receptor (AT1aR) (YMKLKT) did not bind BK nor signal in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Previously we have found that both the AT1 and BKB2 receptors contain certain sequences within their cytosolic faces which are irreplaceable with respect to binding of the ligand or interaction with Gαi and Gαq. For example, in BKB2R the IC1 has to contain N63 to continue to bind [Yu et al, 2005]. In the proximal tail BKB2R has to contain KSRE to continue to signal with Gαi and Gαq [Yu et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we have found that both the AT1 and BKB2 receptors contain certain sequences within their cytosolic faces which are irreplaceable with respect to binding of the ligand or interaction with Gαi and Gαq. For example, in BKB2R the IC1 has to contain N63 to continue to bind [Yu et al, 2005]. In the proximal tail BKB2R has to contain KSRE to continue to signal with Gαi and Gαq [Yu et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture and transfections in HEK‐293 cells were performed as described by Yu et al 2005. HEK‐293 cells were cultured in Dulbecco's modified Eagle's medium (DMEM), containing 10% fetal bovine serum supplemented with 50 U/ml penicillin and 50 µg/ml streptomycin at 37°C in a humidified CO 2 (5%) incubator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AngII binding studies in intact aortic endothelial cells were carried out as described by Yu et al 11.…”
Section: Methodsmentioning
confidence: 99%